Tourism Policy Implementation Strategy In Pangandaran District West Java Province - Yagus Triana HS; Soleh Suryadi; Ali Anwar (Doctoral Program of Social Science Pasundan University, 2021)
This research is focused on study on strategy of tourism policy implementation in Pangandaran Regency, with problem formulation: 1) What factors cause tourism policy implementation in West Java Pangandaran regency not yet effective? 2) What policy strategy should be done for tourism policy implementation in West Java Province Pangandaran to be effective?The policy implementation analysis is using A Model of the Policy Implementation recommended by Van Meter and Van Horn (2005), then the theoretical analysis on which to reconstruct policy strategy is collaborative governance strategy, using the level and model of partnership from Wanna (2008) shared vision of participation, networking, and partnership. The research method used qualitative research method with a case study approach. The tourism policy development strategy ineffectiveness in Pangandaran Regency is caused by many factors: 1) The tourism development strategy aim and target in Pangandaran Regency, not yet clearly measurable, 2) Available resources, both human and financial resources in supporting the implementation of tourism development strategy is very minimal, 3) cross-agency coordination and cross-stakeholders made by the Department of Tourism and Culture has not been implemented effectively, 4) Inter-organizational communication, SOP (Standard Operating Procedure), and the working structure of tourism development strategy has not been implemented effectively, 5) Disposition or attitudes of executors related to understanding, capability, commitment and leadership quality in the implementation of tourism development strategy is not optimal,6) Supporting capacity of social environment, economy and politics through DPRD and other SKPD support not yet optimal, 7) No clarity and normative certainty regarding the institutions responsible for the tourist areas management of. ping tourism in Pangandaran Regency of West Java Province is using collaborative governance strategy.